Subjective and Objective Assessments of Post-traumatic Olfactory Dysfunction - Limphaibool, Nattakarn; Iwanowski, Piotr; Kozubski, Wojciech; Swidziński, Teodor; Frankowska, Anna; Kamińska, Ilona; Linkowska-Swidzińska, Kamila; Sekula, Alicja; Swidziński, Piotr; Maciejewska-Szaniec, Zofia; Maciejewska, Barbara (Frontiers in Neurology, 2020)
Introduction: Traumatic brain injuries are the most common cause of olfactory dysfunction. Deficits in olfaction may be conductive or neurosensory in nature, with varying degrees of impairment resulting in a diminished quality of life and an increased risk for personal injury among patients. The aim of this research is to evaluate the results of the subjective and objective quantitative examinations of olfactory function in a group of patients with post-traumatic anosmia in order to predict its value in identifying olfactory deficits in clinical practice. Material and methods: The present study included 38 patients who reported anosmia or hyposmia caused by a traumatic head injury, and a group of 31 age- and sex-matched controls without olfactory dysfunction or prior history of head injury. The comparison of odor perception and identification of two oils (mint and anise) was assessed with the use of blast olfactometry with cortical olfactory event-related potentials. Results: Subjective olfactory tests revealed anosmia or hyposmia in 94% of patients with head injury-related olfactory dysfunction. Objective tests revealed olfactory event-related potentials from cranial nerve I produced by the stimulation with both mint and anise in 20 patients (52.6%). Olfactory event-related potentials from cranial nerve V produced by the stimulation with mint were registered in 26 patients (68.4%). The lack of any responses, from both cranial nerve I and V, was found in 12 patients (32% of cases). Conclusions: Findings from our study indicate the application of both subjective and objective examinations in the evaluation of patients with olfactory impairment. In the diagnosis of post-traumatic anosmia or hyposmia, objective examinations are particularly useful when the patients’ level of cognition may be impaired or when subjects may be exaggerating their olfactory defects for a secondary gain. The diagnosis of damage to the olfactory system, specifically in the receptive part of the olfactory pathway, can be established in patients who showed reduced amplitudes or absent cortical responses in addition to absent odor identification and perception threshold in the subjective examination.